PERBEDAAN HASIL BELAJAR SISWA DITINJAU DARI MOTIVASI BELAJAR SISWA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT - Saputra, Rangga Handhika (JSTT, 2016)
This research aim to descript the Differences in student learning outcomes in terms of student motivation using type of STAD cooperative learning model and NHT Cooperative Learning model. This way quantity research. The research sample was the grade VII I student of SMPN 2 Palu as first experiment class and grade VII E student of SMPN 2 Palu as second experiment class. This research was used anquet instrument for student’s motivation and test for student leraning outcomes. Data analysis was two way analysis of variance. The result showed that : (1) there are not different the result of student learning, between student was thought by cooperative learning model STAD and student was thought by cooperative learning model NHT, (2) there are not different student motivations (had high, high, had low) between student was thought by STAD cooperative learning model and student was thought by NHT cooperative learning model judging from the results of student learning, (3) there are not interaction between student motivations (had high, high, had low) with tudent was thought by STAD cooperative learning model and student was thought by NHT cooperative learning model.